Monoclonal antibodies from B cells of patients with anti-MDA5 antibody-positive dermatomyositis directly stimulate interferon gamma production. Issue 130 (June 2022) - Coutant, Frédéric; Bachet, Rafael; Pin, Jean-Jacques; Alonzo, Marina; Miossec, Pierre
Abstract: Anti-melanoma differentiation-associated gene 5 (MDA5) antibody (Ab) positive dermatomyositis (anti-MDA5 DM) is a rare entity associated with poor prognosis and multiple immunologic abnormalities. These include the presence of autoAbs and deleterious interferon (IFN)-gamma production in the severe form of the disease. Here, we show that the autoAbs profile differs between patients, depending on disease severity, and that autoAbs from B cells of patients directly stimulate IFN-gamma production by peripheral blood cells. Serum of 29 anti-MDA5 DM patients were analyzed by indirect immunofluorescence (IIF) on Hep-2 cells, to identify patterns associated with poor outcome. Seventeen (59%) serum gave a specific cytoplasmic MDA5 pattern on Hep-2 cells, while 12 (41%) gave an unspecific pattern. Specific MDA5 pattern was associated with a higher risk to develop interstitial lung disease (p = 0.003). Monoclonal autoAbs were generated from B cell clones of two patients with extreme clinical presentation, one who developed a lethal form of the disease, and the other with a favorable outcome. Supernatants of the autoreactive B cell clones that gave an IIF cytoplasmic pattern were tested for their abilities to stimulate IFN-gamma production by peripheral blood cells. Out of 120, 000 B cell clones analyzed, 12 produced monoclonal Abs that triggered direct IFN-gamma secretion by peripheral blood cells, by a monocyte-dependent mechanism. None of them was directed against the MDA5 antigen. Altogether, these findings demonstrated that autoAbs other than the highly specific anti-MDA5 Ab are direct contributors of the IFN-gamma upregulation that is linked to the severity of the disease. Highlights: Dermatomyositis with anti-MDA5 antibodies is a life-threatening autoimmune disease. The disease is characterized by autoantibodies, and deleterious IFNγ production. Several autoantibodies directly stimulate IFNγ production by peripheral blood cells. Targeting stimulatory autoantibodies could be a promising therapeutic strategy.